Customer involvement in designing new services : a framework for management - Tyynelä, Maria (My University, 2019)
The significance of the service sector is growing globally and consequently, so is the interest towards new service development. Extant research on new service development has recognized the multiple benefits of involving customers in service development projects. However, customer involvement in new service development (NSD) is a fragmented research area and the management of customer involvement is considered difficult in practice. The purpose of this thesis is to construct a management framework for customer involvement in NSD, zooming into the early stages of NSD. The theoretical framework of this study combines themes from a wide range of service research domains, such as service innovations, new service development and customer involvement in NSD. The research is conducted as a qualitative single case study for a Finnish company. The study employs a constructive research approach due to the integrative nature of the research purpose. The primary data was collected with seven individual semi-structured interviews across two interview groups. Literature on NSD and customer involvement in NSD was utilized as the basis of the analysis. Interview data was color-coded thematically and analysed in reflection with the theoretical framework. Results show that customer involvement is an important success factor in NSD. It is overall a multi-dimensional phenomenon, which should be managed properly in order to maximize its benefits. The main findings of this thesis are presented as the management framework and a list of action proposals. The construct of the thesis – the management framework – is built based on the theoretical framework and the findings of the study. The cyclic and iterative management framework combines theories of NSD and customer involvement with service design tools and emphasizes the selection and recruiting of customers.
Keywords: service development, service design, customer orientation